Functional characterization of the adenosine receptor mediating inhibition of intestinal secretion. - Hancock, D L (1995)
1. Previous studies have shown that the mixed A1/A2 adenosine agonist 5'-N-ethylcarboxamido-adenosine (NECA) inhibits intestinal fluid secretion which is thought to contribute to its antidiarrhoeal effect in the rat. The aim of this study was to characterize the adenosine receptor mediating this antisecretory effect via functional studies using a range of selective agonists and antagonists and by applying the pharmacological criteria of relative agonist and antagonist potencies. 2. Adenosine agonists and antagonists were administered i.v. to anaesthetized rats. Intestinal secretion was then stimulated by i.a. infusion of vasoactive intestinal peptide (VIP, 0.8 microgram min-1) and the net fluid transport across the wall of the jejunum was measured by a recirculation technique. 3. The rank order of agonist potency to reduce the response to VIP was: NECA > N6-cyclopentyladenosine (CPA) > R-N6-(2-phenylisopropyladenosine) (R-PIA) > S-PIA > chloroadenosine (2-CADO) > 2-phenylaminoadenosine (CV-1808). This order best complies with the rank order of agonist potency that represents activation of the recently described A2B receptor: NECA > 2-CADO > R-PIA = CHA > S-PIA > = CV-1808 > = CGS-21680. The most potent agonists (NECA, CPA and RPIA) had ED50 values in the low microgram range. 4. The anitsecretory action of NECA (submaximal dose of 40 micrograms kg-1) was antagonized equally (approximately 50%) by the selective adenosine antagonists 8-cyclopentyl-1,3-dipropylxanthine (DPCPX, 0.1 mg kg-1) and 8-phenyltheophylline (8-PT, 0.1 mg kg-1). This equipotent activity indicates the presence of an A2 and not an A1 receptor.(ABSTRACT TRUNCATED AT 250 WORDS)